Pronunciation Recognition of –ed Ending Words by the Students of English Education Study Program of the University of Bengkulu - Khinanti Giantari; Syafrizal Sabarudin; Zahrida Zahrida (Universitas Bengkulu, 2020)
This research concerned with the English Education Study Program students’ recognition in pronouncing –ed ending words and the English Education Study Program students’ recognition of different enrollments. This research was a descriptive quantitative research. In this research, form of –ed ending pronunciation test of written sentences was used. The words used in the test items which consist of 40 questions. The data of this research was analyzed by using qualitative and quantitative method. The results of this research shows that the recognition of the English Education Study Program students in pronouncing –ed ending words was low with 46.6 of the average mean score. It confirmed the previous study on the ability in pronouncing morphophonemic or –ed ending words by Ningrum (2019) which conducted in the same place. Furthermore, comparison of the test result among three enrollments of samples shows that different mean score of first and third semester is 1.6 points. It is similar to the different mean score of the first and fifth semester students is 1.4 points. While, the different mean score of the fifth and third semester students is 3 points. It can be concluded that there are not any significant differences between them.